Exploring adolescent views of body image: the influence of media. (March 2013) - Spurr, Shelley; Berry, Lois; Walker, Keith
<x xml:space="preserve">Abstract</x> The purpose of this article is to present findings from two parallel qualitative studies that used focus groups to explore adolescent views of psychological wellness and healthy bodies. Nine focus groups were held with 46 adolescents aged 16–19 years from two Mid-Western Canadian high schools. Both studies were designed with an interpretive humanist perspective and then a 6-step thematic approach was used to analyze the data. Common themes emerging in the focus group discussions in both studies included the negative impact of media on adolescent body image and pressure to conform to the Western views of physical appearance. These findings illustrate the need for nurses to understand the influence of the media on adolescents' views of their body image and to incorporate protocols for assessment, education, and counseling of adolescents on the healthy usage of media into their pediatric clinical practice. Through consistent participation in the development and implementation of health policies, nurses play a critical role in supporting adolescents to develop healthy views of body image.